XÁC ĐỊNH CHUYỂN ĐỘNG HIỆN ĐẠI ĐỚI ĐỨT GÃY LAI CHÂU - ĐIỆN BIÊN TỪ SỐ LIỆU ĐO GPS (2002- 2004) - Tô, Trần Đình; Hải, Vy Quốc (Vietnam Journal of Earth Sciences, 2017)
A GPS Network of 6 stations has been installon Lai Chau-Dien Bien Fault Zone and occupied 3times (2002, 2003, 2004) using simultaneously Trimble dual frequency 4000 SSi receivers in four sessions of 24 hours for every campaign.The paper describes in detailed independent processing of the 2002 and 2004 campain observation data using both BERNESE 4.2 arid GPS urvey 2.35 GPS Softwares. Two result sets ofthe computation are of high quality and asummedto be equivalent under point position coordinatesand their accuracy. Nevertheless, only horizontal motions of the fault could be now estimated.An analysis of these outcomes allows to concludenowadays left slip of the Lai Chau-Dien Bien Faultwith relative velocity of about 3 +- 1,5 mm/year.The result should be considered as primarybecause the observation data spanned only two years. That's why new obervations on the networkare necessary in near future.